Analisis Faktor-Faktor Determinan Dalam Pemilu : Suatu Tinjauan Terhadap Perspektif Mahasiswa PPKN Unimed Stambuk 2023 - Fariz Aditya; Alissa Putri Simbolon; Ertika Susanti Pasaribu; Eka Putriani Sihombing; Julia Ivanna (Universitas 17 Agustus 1945 Semarang, 2024)
General elections (Pemilu) are a key element in strengthening the foundation of democracy, where voter participation, especially among students, plays a crucial role in shaping the direction of a country's democracy. This research explores the determinant factors influencing the decisions of young voters, particularly students in the Civic Education Program (PPKN) at Universitas Negeri Medan (Unimed) with Stambuk 2023. The primary focus of this study is to understand the motivations and barriers to young voter participation in elections. The research aims to analyze determinant factors in general elections, emphasizing the perspective of PPKN students at Unimed with Stambuk 2023. Through a survey approach and quantitative research design, the study reveals that student voters tend to make decisions based on in-depth understanding, personal beliefs, and active participation in political activities. These findings provide profound insights into the dynamics of student voter preferences and decision-making. Campaign strategies that prioritize effective communication regarding political parties, candidates' track records, visions and missions, work programs, and freedom of expression can enhance the potential for garnering support. Further understanding of personal values and individual experiences is also crucial in designing campaigns that align with the expectations and values of young voters. With this deeper understanding, the research aims to provide a foundation for formulating relevant policy recommendations to increase young voter participation at the university level.